1992
DOI: 10.1007/bf00170203
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of nitrifying bacteria in porous pellets of urethane gel for removal of ammonium nitrogen from waste-water

Abstract: The effects of immobilizing materials on the activity of nitrifying bacteria and removal of ammonium nitrogen (NH4-N) from waste-water by immobilized nitrifying bacteria were investigated using six urethane prepolymers. With a urethane prepolymer containing 2.27% free isocyanate, a high activity yield of nitrifying bacteria was obtained. There was a drastic improvement over the conventional method of immobilization by acrylamide in the activity yield. Inorganic synthetic waste-water was treated at a high loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The combined use of nitrifying bacteria and denitrifying bacteria is effective to remove ammonia; it produces nitrogen gas from ammonia (Sumino et al, 1992). The combined use of nitrifying bacteria and denitrifying bacteria is effective to remove ammonia; it produces nitrogen gas from ammonia (Sumino et al, 1992).…”
Section: Removal Of Ammonia From Sewagementioning
confidence: 99%
“…The combined use of nitrifying bacteria and denitrifying bacteria is effective to remove ammonia; it produces nitrogen gas from ammonia (Sumino et al, 1992). The combined use of nitrifying bacteria and denitrifying bacteria is effective to remove ammonia; it produces nitrogen gas from ammonia (Sumino et al, 1992).…”
Section: Removal Of Ammonia From Sewagementioning
confidence: 99%
“…How to effectively keep the high activity of nitrifying bacteria pellets for long-term storage is an urgent problem in its technology application [5] [6]. Because active decay of nitrifying bacteria in the preservation process is complex, it depends on lots of environmental factors [7]. Few studies on the decline of nitrifying bacteria and the research of immobilized nitrifying bacteria products preservation process have not been reported [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conventional processes, the embedding immobilization technology has several advantages [38][39][40] such as enhanced degradation rate, protection of microbes against toxicity, operation stability, protection from extreme conditions and economic. [41][42][43] A considerable number of previous studies on immobilized microbial technology are directed towards the treatment of high-concentration ammonia-nitrogen wastewater or wastewater containing toxic and harmful compounds.…”
Section: Introductionmentioning
confidence: 99%